WACANA KONSEP HUKUM PROGRESIF DALAM PENEGAKAN HUKUM DI INDONESIA - Ravena, Dey (Jurnal Wawasan Yuridika, 2010)
Laws are for humans, not vice versa, thus paradigms should be used in studying law. This is the entrance and the point of view (point of view) which will affect all aspects of our learning about progressive law. People who use a different point of view will also generate learning about the law differently. Acknowledging the presence of humans as a major stakeholder in the law would place them in line with legal regulations, if not, even on higher ground.Admittedly, that it is not easy to be realized or implemented. Much easier when we only have to deal with any regulations.Keywords: Progressive Law Human - Law - Enforcement